(NzEMNAQ KORA WOSTO^NOJ ^ASTI bALTIJSKOGO ]ITA (B/s - (NkRATC(B, (NkAUKO oTTOWI^s; (NgLEBOWICKIJ(B, (Nw(B.(Na(B.s; (NbYLINSKIJ(B, (Nr(B.(Nw(B.s; (NgLEBOWICKIJ(B, (NwIKTOR aNDREEWI^s ((Nl(B. :s (NnAUKA(B. (NlENINGR(B. (NOTD(B-(NNIE(B,s, 1978)
(NbIBLIOGR(B.: (NS(B. 211-226s
(Nan sssr(B. (NoTD(B. (NGEOLOGII(B, (NGEOFIZIKI(B, (NGEOHIMII(B. (NnAU^NYJ SOWET PO KOMPLEKSNYM ISSLEDOWANIQM ZEMNOJ KORY I WERHNEJ MANTIIs
Keywords: (NbALTIJSKIJ ]ITs; (NgEOLOGIQs; (NzEMNAQ KORAs